ANALISIS YURIDIS SYARAT PENCALONAN KEPALA DESA DALAM PENYELENGGARAAN PEMERINTAHAN DESA (KAJIAN PASAL 33 HURUF D UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA) - Iber dedy Kornel Tanesib; Lelly Muridi Zham-Zham; Rizkina Mewahni (Consilium: Education and Counseling Journal, 2026)
Village government is at the forefront of public service delivery and community affairs consolidation in Indonesia, encompassing both formal and informal aspects such as customs and traditional rights. In a decentralized system, villages have genuine autonomy as self-governing communities authorized to manage their own affairs. However, the enactment of Law Number 6 of 2014 concerning Villages (Village Law) brought significant changes, particularly in the village head election system (pilkades), including the determination of candidacy requirements. This paper analyzes the legal requirements for village head candidacy, focusing on Article 33 letter d of the Village Law concerning the minimum educational qualification of Junior High School (SMP) or equivalent. This research is a literature study that also examines the implications of this provision for future village governance, considering the complexity of the village head's duties that require in-depth understanding in various fields. Using a case study method, this research aims to evaluate whether the minimum educational requirements stipulated in Article 33 letter d of the Village Law are relevant and adequate to ensure the quality of village leadership that is effective and responsive to community dynamics and development demands.